1992
DOI: 10.1002/chin.199229013
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Study of the Lithium Intercalation/Deintercalation Processes into V2O5 by Linear Voltammetry at Slow Sweep Rates.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…It was reported that the potential plateau was thought to result from the coexistence of two phases, and was observed at 3.4, 3.2 and 2.4 V for crystalline Li x V 2 O 5 [2]. The abrupt potential reduction was associated with the completion of phase transformation from d phase to c phase, which led to a capacity loss at the cathode due to an irreversible structural transformation [13]. The absence of a potential plateau and an abrupt potential reduction in the charge/discharge curve of the amorphous Li x V 2 O 5-y thin film suggests that the thin film maintained a single phase in the whole composition range (x = 0-2.0) without phase transformation during charge/ discharge.…”
Section: Resultsmentioning
confidence: 97%
“…It was reported that the potential plateau was thought to result from the coexistence of two phases, and was observed at 3.4, 3.2 and 2.4 V for crystalline Li x V 2 O 5 [2]. The abrupt potential reduction was associated with the completion of phase transformation from d phase to c phase, which led to a capacity loss at the cathode due to an irreversible structural transformation [13]. The absence of a potential plateau and an abrupt potential reduction in the charge/discharge curve of the amorphous Li x V 2 O 5-y thin film suggests that the thin film maintained a single phase in the whole composition range (x = 0-2.0) without phase transformation during charge/ discharge.…”
Section: Resultsmentioning
confidence: 97%